Football for people with cerebral palsy: scope review (Research, Society and Development, 2021)
Purpose: to describe the results of studies that address soccer for people with cerebral palsy, demonstrating the evolution of research over the years in terms of performance, sport classification and evaluation instruments. Methodology: a scope review was carried out using the PubMed, Web of Science, Scielo and Scopus databases through access to Capes journals. The descriptors used for the search were: "soccer for people with cerebral palsy" and "7 football", both descriptors in Portuguese, Spanish and English. Results and discussion: in studies that performed physical assessments and performance, they identified that athletes of higher sports classes (FT3) showed better results when compared with athletes from lower sports classes (FT1), whether in tests of agility, jumping height or sprint tests. In studies that investigated the sports classification, they identified a clear relationship between performance and sport class, some of the performance tests are currently used in the classification process. In addition, there are few studies on sports injuries in PC football. Final Considerations: much of the research on PC football has been focused on evaluating the motor performance, but there is still a large field to be explored regarding sport classification and incidence and prediction incidence of injuries. The development of these three areas of knowledge will further strengthen the modality.